2020
DOI: 10.48550/arxiv.2009.12757
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Precision orbital dynamics from interstellar scintillation arcs for PSR J0437-4715

Daniel J. Reardon,
William A. Coles,
Matthew Bailes
et al.

Abstract: Intensity scintillations of radio pulsars are known to originate from interference between waves scattered by the electron density irregularities of interstellar plasma, often leading to parabolic arcs in the two-dimensional power spectrum of the recorded dynamic spectrum. The degree of arc curvature depends on the distance to the scattering plasma and its transverse velocity with respect to the lineof-sight. We report the observation of annual and orbital variations in the curvature of scintillation arcs over… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
(83 reference statements)
0
5
0
Order By: Relevance
“…However, early studies by Hemberger and Stinebring [58] already showed how these phenomena can impact timing significantly. Turning this around, Reardon et al [121] showed how scintillation arcs can actually be useful for timing, as they can provide independent constraints on timing-model parameters. The study of how to use scintillation arcs, or what effects they really do have on PTA experiments, has only just begun, so at present their impact is not fully clear yet.…”
Section: Iism Studiesmentioning
confidence: 99%
“…However, early studies by Hemberger and Stinebring [58] already showed how these phenomena can impact timing significantly. Turning this around, Reardon et al [121] showed how scintillation arcs can actually be useful for timing, as they can provide independent constraints on timing-model parameters. The study of how to use scintillation arcs, or what effects they really do have on PTA experiments, has only just begun, so at present their impact is not fully clear yet.…”
Section: Iism Studiesmentioning
confidence: 99%
“…We have restricted this plot to source brightness temperatures in the range 10 11 − 10 12 K. 2013) that very similar screens could also be responsible for the parabolic arc phenomenon observed in the secondary spectra of certain radio pulsars (Cordes et al 2006;Walker et al 2004). It remains to be seen whether filamentary screens of the kind revealed in this paper can account for other properties of the parabolic arcs, such as their occurrence rate and the scattering anisotropy (Reardon et al 2020).…”
Section: Physical Propertiesmentioning
confidence: 79%
“…Several scintillating pulsars show variability in their diffractive scintillation timescale, which can be modelled as in Rickett et al (2014) and Reardon et al (2019) to provide more precise measurements of 𝑖 and improve the mass constraints. Modulation in the curvature of scintillation arcs could also be detected in some pulsars and provide a more precise measurement of 𝑖 and Ω than the scintillation timescale (Reardon et al 2020).…”
Section: Discussionmentioning
confidence: 99%